Evaluating the feasibility of using rapid prototyping technology for creative technology LTD products - Cheung, Kim Kwong. (2008)
Rapid Prototyping (RP) is the production of a physical model from a computer model without the need of any jig or fixture and NC programming. Rapid prototyping has been in evidence for the past 10 years. One of the main benefits of RP is the ability for the manufacturer to verify a design in a matter of hours after completion of the CAD data. For technology companies, like Creative Technology Ltd (CTL) in a high competitive environment, making the transition from product concept to production as fast as possible is critical. The more planning that goes into early stages of product development like prototyping, the greater the chances of lessening the time, errors and cost related to a project. In this report, a product (Multimedia Remote Controller) is selected as a case study for evaluating the advantages and disadvantages for different RP technologies, and the feasibility of using RP technology for Creative Technology Ltd products.